A Senior Teacher's Implementation of Technology Integration - Tsai, Hsien-Chang (International education studies, 2015)
This study investigated whether a senior teacher with many years of teaching experience, despite lacking adequate technology skills or contending with other barriers, can sufficiently implement technology integration in the classroom. The research was conducted between October 2013 and January 2014 and was focused on a junior high school biology teacher with 17 years of instructional experience. A qualitative method involving semistructured interviews and classroom observation of 4 conducted lessons was used to explore the teacher's implementation of technology integration. The analytical results showed that the teacher's perspectives on technology integration ranged from "technology as a tool for teaching" to "technology as a learning activator." Moreover, external factors such as poor technology management affected the teacher's implementation of technology integration. In addition, the teacher developed a technological-pedagogical-content-knowledge base, building on current pedagogical content knowledge. The findings of this study enhance the general understanding of the development and implementation of senior teachers regarding technology integration, as well as the integration of subject content and pedagogical knowledge in teaching.